Analisis Kenerja Mikrokontroler dalam Sistem Data Paisen di Rumah Sakit Umum Kisaran - Dinda Sri Damayanti (STIKes Ibnu Sina Ajibarang, 2025)
Microcontrollers play a vital role in managing patient data systems within hospital environments, including at Kisaran General Hospital. A microcontroller-based data management system facilitates the automation of patient data recording and processing in real time, enhancing both accuracy and efficiency. This study aims to analyze the performance of microcontrollers in a patient data system by evaluating parameters such as processing speed, data accuracy, and system stability. The implementation involves an Arduino Uno microcontroller integrated with sensors and data processing software. Experimental results demonstrate the system's ability to process patient data quickly and accurately, contributing to the operational efficiency of the hospital. These findings highlight the potential of microcontroller technology as a modern solution for patient data management in healthcare settings.